University students' drinking motives : relationship with alcohol use - Maphisa, Jabulani Maphisa (Rhodes University, Faculty of Humanities, Department of Psychology, 2015)
Alcohol use among university students is a worldwide social and clinical reality. Understanding and addressing this phenomena is an imperative recognised by the government of South Africa and its Higher Education institutions, where student drinking has a plethora of negative consequences. This study builds on the work of Young and de Klerk (2012) with Rhodes University students by adding drinking motives to their findings of demographic correlates. The motivational model of alcohol use (Cox & Klinger, 1988) posits that drinking motives are a proximal predictor of alcohol use. The model further delineates four drinking motives (social, enhancement, coping, and conformity) which are hypothesized to lead to phenomenological distinct patterns of alcohol use. An online survey method was utilized to collect data and a representative sample of 501 students participated. Descriptive and inferential statistics were computed to address five research questions: (1) to establishing the current alcohol use trend; (2) to investigate the demographic factors associated with alcohol use; (3) to describe students' drinking motives; (4) to explore the correlates of drinking motives; and, finally, the primary aim was (5) to investigate whether students' drinking motives predicted alcohol use when controlling for the effects of descriptive drinking norms and demographic variables. The results indicate that 68.5% of participants currently consume alcohol, and 51.0 % of these drinking students consume five or more drinks during a drinking session. 20.7 % of the drinking students used alcohol at the harmful or alcohol dependent levels. Increased alcohol use was associated more with males, undergraduates, early onset drinkers, more disposable income, and students' perceptions of their peers' drinking. Students endorsed enhancement motives marginally more than social motives, followed by coping and conformity motives. Males, early onset drinkers, black students, and at risk (of alcohol use disorders) students endorsed more motives, especially social and enhancement motives. Of primary concern was the role of drinking motives on alcohol use after controlling for the effects of descriptive drinking norms. The four block hierarchical regression model which was run explained 38% of the variance in alcohol use. Drinking motives, particularly enhancement motives, displayed a statistically significant impact on alcohol use adding 11% to the variance. Additionally, age of alcohol use onset, monthly pocket money, age, and gender predicted alcohol use separately. The results of this study indicate that alcohol use has multi-factorial influences. Of note, the results confirmed the motivational model of alcohol use by indicating that alcohol use is partially motivational and that drinking behaviour is not a unitary phenomenon but instead it represents heterogeneity based on the affective change individuals anticipate to gain by drinking. The high binging rate (51%) among this sample may speak to the greater endorsement of enhancement motives, which have been shown in previous studies to be associated with heavy drinking. Enhancement motives are attempts to attain positive affect which, due to the psychoactive properties of alcohol, require greater consumption and intoxication. Additionally, as a result of the greater quantities of alcohol, individuals who drink for enhancement motives would be more prone to alcohol consequences. The results suggest that a multi-level intervention framework targeting individual students, the university community, and the surrounding community, is indicated. Furthermore, intervention may be tailored-made to address specific drinking motives.
Keywords: College students -- Alcohol use -- South Africa -- Grahamstown; College students -- South Africa -- Grahamstown -- Conduct of life; College students -- South Africa -- Grahamstown -- Attitudes; Motivation (Psychology) -- South Africa -- Grahamstown; Social integration -- South Africa -- Grahamstown; Adjustment (Psychology) -- South Africa -- Grahamstown; Conformity -- South Africa -- Grahamstown